1968
DOI: 10.1161/01.cir.37.4.566
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomic Atrial Connections Between Sinus and A-V Node

Abstract: The morphology of the sinus and atrioventricular (A-V) nodes of human hearts was studied and connecting pathways between these nodes were sought. The cells of both nodes differed from ordinary atrial and ventricular myocardium in respect to size, shape, number, and arrangement of cytoplasmic organelles. Using the criteria of fiber-to-fiber connection, shown by means of serial histological sectioning, this study confirmed previous reports of three pathways between the sinus and A-V nodes in the human heart. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Rarely, these bypass fibers penetrated directly into the crest of the interventricular septum. Such bypass tracts, as a feature of the norm al A V node, have not been found by others (9,16,126). Because of the functional implications of the term bypass tract, namely that impulses from the atrium can be transmitted without delay to the beginning of the atrioventricular bundIe or the ventricular septum, it is useful to use a strict definition.…”
Section: Atrial Overlay Fibers and Bypass Tractsmentioning
confidence: 94%
“…Rarely, these bypass fibers penetrated directly into the crest of the interventricular septum. Such bypass tracts, as a feature of the norm al A V node, have not been found by others (9,16,126). Because of the functional implications of the term bypass tract, namely that impulses from the atrium can be transmitted without delay to the beginning of the atrioventricular bundIe or the ventricular septum, it is useful to use a strict definition.…”
Section: Atrial Overlay Fibers and Bypass Tractsmentioning
confidence: 94%
“…Successful experiments were made on hearts from 28 dogs of the following age ranges (7 per group): 1-7 days (newborn), 1-12 weeks (puppy), and two groups of adult dogs, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Circulation Research, Vol. XXIX, AuguU 1971 months, and over 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…Meredith and Titus (10), on the other hand, summarized their results by stating that their study did not reveal any striking structural differences between cells composing "specific pathways and ordinary atrial cells," and commented that the question whether there are atrial conducting pathways is, in part, one of semantics. Functional evidence used to support the idea of specialized atrial tracts has been largely based on differences in the shape of intracellular action potentials (11)(12)(13) and in the sensitivity of cells to changes in external potassium (14).…”
mentioning
confidence: 99%
“…1965;H udson, 1967;T ruex et a i, 1967;Verhaeghe and Van der Hauswaert, 1967;Merideth andTrrus, 1968: H romada andVoboril, 1970;Bojsf.n-M oller and T ranum-Jensen, 1972]. When searching for sources in the literature dealing with the cardiac conduction system, the Received: September I, 1975. authors only found one single paper dealing with the lymph of this tissue, actually of the bundle of His [Curran, 1909]: here, this author describes the special perilymphatic space surrounding the atrio-ventricular bundle.…”
Section: Introductionmentioning
confidence: 99%